Penghapusan Jasa Pendidikan dari Jasa Tidak Kena Pajak Berdasarkan Undang-Undang Nomor 7 Tahun 2021 tentang Harmonisasi Peraturan Perpajakan - Farina Firda Eprilia (Jurnal Hukum Lex Generalis, 2022)
One of the biggest contributions of Indonesian taxation comes from Value Added Tax for both goods and services. This study uses a normative juridical method, sourced from secondary data in the form of positive law, and begins deductively by examining all laws and regulations related to the legal issues studied. This study found that based on Law Number 7 of 2021 concerning Harmonization of Tax Regulations, educational services that were not previously taxed were officially removed so that their status became taxable services. The policy has drawn criticism from various levels of society because the government is considered to have not heeded the principle of prudence and the principle of public interest.